Evaluasi Pelaksanaan Kurikulum Tingkat Satuan Pendidikan (KTSP) Sekolah Menengah Pertama (Smp-Mts) di Kota Pekalongan Tahun 2011 - Muhammad Ali Gunawan; Fajru Sidqi; M. Haryanto; Dwi Eddy Wibowo (Universitas Pekalongan, 2013)
This study aims to determine and describe and evaluate: 1) Implementation of the School Based Curriculum (SBC) in Junior High School in Pekalongan from the context, input, process, and product; 2) the obstacles faced by schools in implementation of School Based Curriculum (SBC) in junior High School in Pekalongan. From 35 Junior high schools in Pekalongan, 10 (ten) schools was taken as the sample in this study using multistage sampling technique. Data analysis techniques used were descriptive statistics for the primary data (quantitative) and qualitative for secondary data. This study shows that: 1) viewed from 8 national education standards, the implementation of School Based Curriculum (SBC) in Junior High School in Pekalongan fall into the category of